Immune biomarkers for predicting response to adoptive cell transfer as cancer treatment - van Belzen, Ianthe A E M; Kesmir, Can (Springer Science and Business Media Deutschland GmbH, 2019)
Adoptive cell transfer (ACT) is a form of personalised immunotherapy which has shown promising results in metastasised cancer. For this treatment, autologous T lymphocytes are selected and stimulated in vitro before re-administration in large numbers. However, only a fraction of patients benefit from ACT, and it is not yet known what biomarkers can predict treatment outcome. In this review, we describe what tumour characteristics are associated with response to ACT. Based on the current knowledge, the best candidate biomarker for a good anti-tumour response seems to be a large number of neoantigens with a homogeneous distribution across the tumour in combination with sufficient MHC-I expression level. Additionally, it is necessary to be able to isolate a diverse population of T cells reactive to these neoantigens from tumour tissue or peripheral blood. Additional promising candidate biomarkers shared with other cancer immunotherapies are a large number of tumour-infiltrating cytotoxic and memory T cells, normal levels of glycolysis, and a pro-inflammatory cytokine profile within the tumour. Intense research in this field will hopefully result in identification of more biomarkers for cancers with low mutational load.
Keywords: Adoptive Transfer/methods; Antigen Presentation; Antigens, Neoplasm/immunology; Biomarkers/blood; Cytokines/analysis; Humans; Mutation; Neoplasms/immunology; T-Lymphocytes, Cytotoxic/immunology; Tumor Escape; Tumor Microenvironment; SDG 3 - Good Health and Well-being